Relación de actividad física y hábitos alimentarios con el estrés académico en pandemia por COVID-19 - Bautista Valderrama, Luis Andy (2021)
To determine the relationship between physical activity and eating habits with academic stress in medical students at the National University of Trujilloin a COVID-19 pandemic. Materials and Methods: Non-experimental study, descriptive correlational type and cross-sectional; evaluated in 174 undergraduate medical students from the National University of Trujillo in a COVID-19 pandemic. The short version IPAQ questionnaire, the university eating habits questionnaire and the SISCO-SV inventory were applied. Results: It was found that 57.5% of the students presented low physical activity; 70.7%, adequate eating habits; and 74.4%, moderate academic stress. In the statistical analysis using the Chi square test, the relationship between physical activity and academic stress was obtained with a value of p = 0.0659; on the other hand, the relationship between eating habits and academic stress was obtained with a value of p = 0.0006. Conclusions: There is no significant relationship between physical activity and academic stress. However, a significant relationship was found between eating habits and academic stress in undergraduate medical students at the National Universityof Trujillo.